Analisis Kesejahteraan Keluarga Usaha Budidaya Ikan Keramba Di Danau Teluk Kota Jambi - M Zahari; Hasminidiarty Hasminidiarty; Adria Wuri Lastari (Universitas Batanghari Jambi, 2021)
This study took place in Teluk Lake Jambi City, with the aim of: (1) knowing the condition of the cage fish farming business based on the number and area of cages owned, the workforce used, business capital, as well as production results and income, (2) Analyzing the level of family welfare as measured by the income level of fish farmers. Cages, and (3) to analyze the effect of working capital, labor, cage area and production on the welfare of the family of caged fish farming business. This research is a survey research on a sample of 50 respondents of caged fish cultivators in Teluk Lake, Jambi City. Data analysis used multiple regression, and the hypothesis was tested by F test and t test. The results showed that most of the cage fish farmers used their own capital, employed around 1-2 people, the average cage area was 74.74 m2 per farmer, and the production that could be produced reached 2.08 tons per harvest. The income received by farmers has exceeded the Jambi City Minimum Wage. The results of hypothesis testing prove that capital, labor, cage area, and production affect the welfare of family cage fish farming in Teluk Lake, Jambi City. Given that it is important to develop cage fish cultivation in order to improve family welfare, a government policy is needed to provide capital assistance and foster cage fish farming businesses in Teluk Lake, Jambi City.